CLONAL DIFFERENCES OF BLACK POPLAR CUTTINGS FOR MORPHO- PHYSIOLOGICAL AND BIOCHEMICAL RESPONSES TO SOIL WATER DEFICITS - M. Topić; M. Borišev; S. Orlović; M. Tomičić; M. Župunski; N. Nikolić; S. Pajević; B. Krstić; A. Pilipović (Journal of Animal and Plant Sciences, 2013)
Five black poplar clones were subjected to three different soil water regimes (well-watered and two water-stressed treatments) to evaluate their morpho-physiological and biochemical responses to water deficits. Plants were grown in a semi controlled environment (greenhouse) by soil culture method. The three-month-old plants were exposed to 90-70%of maximum soil water saturation - control, mild drought followed by recovery of optimal soil water saturation (90-40%) and severe drought (50-40% of soil water saturation) for 21 days. Prolonged drought caused reduction in photosynthetic (A) and transpiration (E) intensity in all clones, but after recovery these parameters were enlarged considerably. Instantaneous water use efficiency (WUEi) was significantly increased under conditions unfavorable for A and E, where genotypes IX/30 and I/2 showed the highest values. The best recovery of A and WUEi exhibited genotype I/2. Proline accumulation in leaves was increased with the increasing intensity of drought, whereas VII/25 and I/2 showed better osmotic adjustments and higher drought tolerance than the other examined clones. No direct correlation was found between water deficit level and malondialdehyde (MDA) content in genotypes IX/30 and X/32, while the other clones showed significant MDA accumulation in one or both drought treatments. Water deficits significantly slowed down apical growth and shoot height growth in all clones except in X/32, while VII/32 and X/32 showed similar number of leaves during all treatments with no significantly differences among values per clone. The obtained results provide clear evidence for clonal differentiation in their responses to water deficiency in all examined parameters.
Keywords: Black poplar genotypes; soil water deficits; recovery; morpho-physiological parameters; biochemical